Asthma control assessment in a pediatric population: comparison between GINA/NAEPP guidelines, Childhood Asthma Control Test (C‐ACT), and physician's rating. Issue 6 (12th April 2014) - Deschildre, A.; Pin, I.; El Abd, K.; Belmin‐Larrar, S.; El Mourad, S.; Thumerelle, C.; Le Roux, P.; Langlois, C.; de, J.
Abstract Background Guidelines recommend regular assessment of asthma control. The Childhood Asthma Control Test (C‐ACT) is a clinically validated tool. Aim To evaluate asthma control according to GINA2006, NAEPP, pediatrician's assessment (PA), and C‐ACT in asthmatic children visiting their ambulatory pediatrician or tertiary care pediatric pulmonologist. Methods Demographic data, treatment, and number of severe exacerbations during the previous year were collected. Control was assessed using (i) strict GINA 2006 criteria, (ii) GINA without taking into account the exacerbation item, (iii) NAEPP criteria, and (iv) PA. Children and parents filled out the C‐ACT. Results Five hundred and twenty‐five children completed the survey (mean age: 7.7 years; 28% ≤ 6 years). 78% had a controller treatment. 58% reported ≥ 1 severe exacerbation. C‐ACT was ≤ 19 in 29.5%. Control was not achieved in 76.5%, 55%, 40%, and 34% according to GINA 2006 guidelines, NAEPP guidelines, GINA 2006 without exacerbation criteria, and PA, respectively. C‐ACT was significantly lower in children ≤ 6 years old (P = 0.002) or with severe exacerbations (P < 0.0001). According to PA, 89% of patients with a C‐ACT > 21 were controlled and 85% of patients with a C‐ACT < 17 not controlled. Conclusion We observed discrepancies between the different tools applied to assess asthma control in children, and the impact of age and exacerbations. Cutoff point of 19 of C‐ACT was not associated with the best performance compared to PA. Assessment of control should take into account symptoms and lung function as suggested by the latest GINA guidelines as well as exacerbation over a long period.